Topology of Magnetic and Velocity Fields at Kinetic Scales in Incompressible Plasma Turbulence. Issue 1 (4th January 2023) - Zhang, J.; Huang, S. Y.; Sahraoui, F.; Andrés, N.; Yuan, Z. G.; Jiang, K.; Xu, S. B.; Wei, Y. Y.; Xiong, Q. Y.; Wang, Z.; Lin, R. T.; Yu, L.
Abstract: The topology of the magnetic and velocity fields at the kinetic scales are investigated in the context of nearly incompressible magnetosheath plasma turbulence. Using the unprecedented high‐resolution data from the Magnetospheric MultiScale mission, the joint probability distribution functions of geometrical invariants characterizing the magnetic and velocity fields gradient tensor at the kinetic scales are computed. The topological features of the magnetic and velocity field gradient tensors and their symmetric component tensors present axisymmetric distribution patterns, indicating that the structure of the plasma turbulence at the kinetic scales are different from those in hydrodynamic and magnetohydrodynamic turbulence. Moreover, a strong correlation between the straining and rotational parts of the magnetic and velocity field gradient tensors was found, which manifests the dominance of sheet‐like structures at the kinetic‐scales dissipation in incompressible plasma turbulence. Plain Language Summary: The terrestrial magnetosheath provides an excellent laboratory to study space plasma turbulence. Thanks to the unprecedented high time resolution data of the Magnetospheric Multiscale mission, the kinetic‐scales structures and dynamic of incompressible magnetosheath plasma turbulence can be investigated. By means of a universal topological classification method in fluid dynamics area, we construct the topological features of both magnetic and velocity field in incompressible plasma turbulence at dissipation scales. Our results show that the distribution of velocity‐field topological structures is different from the other turbulence system, such as hydrodynamic and magnetohydrodynamic turbulence. In addition, we verify that the sheet‐like structures dominate the kinetic‐scales dissipation in the incompressible plasma turbulence. Key Points: The kinetic‐scales topological features in incompressible magnetosheath plasma turbulence are investigated Distribution patterns different from hydrodynamic and magnetohydrodynamic turbulence of velocity‐field topological characteristics are identified Sheet‐like structures dominate dissipation‐scale dynamics in the incompressible plasma turbulence